Think Like Zuck: The Five Business Secrets of Facebook's Improbably Brilliant CEO Mark Zuckerberg (Audio Book) - Donovan, Jeremey (McGraw-Hill, 2013)
Wall Street Journal Bestseller Make Your Mark in the World with the Five Success Principles of the World-Changing Social Media Site If Facebook were a country, it would be the third largest in the world. Facebook accounts for one of every seven minutes spent online. More than one billion pieces of content are shared on Facebook . There's no doubt about it. Mark Zuckerberg's creation has changed the world. Literally. Facebook has singlehandedly revolutionized the way more than one-seventh of the world's population communicates, engages, and consumes information. If you run a business or plan to start one, you're probably asking yourself the same question organizational leaders worldwide are asking: What did Mark Zuckerberg do right? At long last, the answer is here. Think Like Zuck examines the five principles behind Facebook's meteoric rise, presented in actionable lessons anyone can apply-in any organization, in any industry. Written by social business trailblazer Ekaterina Walter, this groundbreaking book reveals the five "P"s of Facebook's success: PASSION -Keep your energy and commitment fully charged at all times by pursuing something you believe in PURPOSE -Don't just create a great product; drive a meaningful movement PEOPLE -Build powerful teams that can execute your vision PRODUCT -Create a product that is innovative, that breaks all the rules, that changes everything PARTNERSHIPS -Build powerful partnerships with people who fuel imagination and energize execution Packed with examples of Facebook's success principles in action-as well as those of Zappos, TOMS, Threadless, Dyson, and other companies- Think Like Zuck gives you the inspiration, knowledge, and insight to make your own mark in the world, to build a business that makes a difference, and to lead your organization to long-term profitability and growth. " Think Like Zuck is a fascinating look at how entrepreneurial vision drives success. If you want more out of work than just a job, if you have the burning desire to build something of lasting value, then this is your guide." -DAVID MEERMAN SCOTT, bestselling author of The New Rules of Marketing and PR "Whether you're a seasoned business executive or the next Mark Zuckerberg in your dorm room right now, this book is a must-read! Two likeable thumbs up!" -DAVE KERPEN, New York Times bestselling author of Likeable Social Media and Likeable Business "True success lies at the place where passion and purpose collide-this book will h...